1970
DOI: 10.1111/j.1476-5381.1970.tb09875.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐acid induced depression of cortical neurones

Abstract: Summary1. The effects of strychnine on the degree of depression of neuronal firing induced by glycine, y-aminobutyric acid (GABA) and 5-hydroxytryptamine (5-HT) have been examined quantitatively. All drugs were applied by iontophoresis to spontaneously active cerebral cortical neurones in the anaesthetized cat. The application of these drugs was continued until a plateau or equilibrium depression was reached. The time taken to reach this steady state was noted. Dose-response curves were then constructed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…The reduction in staining intensity in rostra1 brain regions compared with the spinal cord was due both to a decrease in the number of stained profiles and to a decrease in the intensity of staining of individual the activity of the natural transmitter, and this depression can profiles. Since the structures stained with antisera used in the be selectively blocked by strychnine ; Curtis present study are regions of the postsynaptic specialization (auet al, 1968;Johnson et al, 1970). The addition of the present ditory system: Altschuler et al, 1986;spinal cord: Triller et al, data demonstrating high amounts of glycine in a select popu-1985 and present study; olfactory bulb: present study), smaller lation of presynaptic axons further supports the role of glycine synaptic specializations would result in a smaller fluorescent as a neurotransmitter candidate.…”
Section: Subcellular Localization Of Glycine Immunoreactivitymentioning
confidence: 90%
See 1 more Smart Citation
“…The reduction in staining intensity in rostra1 brain regions compared with the spinal cord was due both to a decrease in the number of stained profiles and to a decrease in the intensity of staining of individual the activity of the natural transmitter, and this depression can profiles. Since the structures stained with antisera used in the be selectively blocked by strychnine ; Curtis present study are regions of the postsynaptic specialization (auet al, 1968;Johnson et al, 1970). The addition of the present ditory system: Altschuler et al, 1986;spinal cord: Triller et al, data demonstrating high amounts of glycine in a select popu-1985 and present study; olfactory bulb: present study), smaller lation of presynaptic axons further supports the role of glycine synaptic specializations would result in a smaller fluorescent as a neurotransmitter candidate.…”
Section: Subcellular Localization Of Glycine Immunoreactivitymentioning
confidence: 90%
“…Strychnine, which in low doses binds selectively to glycine re-ceptors (Young and Snyder, 1974), binds to specific regions of the rat nervous system (Zarbin et al,198 1) and to homologous areas of the human nervous system (Probst et al, 1986). Electrophysiological responses to glycine have been recorded, generally of an inhibitory nature Curtis et al, 1968), and these can be blocked by strychnine (Curtis et al, 1968;Johnson et al, 1970). Pronounced release of glycine from spinal cord slices, but not from cerebral cortex, can be induced with potassium (Mulder and Snyder, 1974).…”
mentioning
confidence: 99%
“…More recently, following the introduction of bicuculline as a specific GABA antagonist, Curtis and his colleagues (Curtis & Felix, 1971) have extended their studies to show that motoneurones are inhibited by at least two separate pathways terminating on two distinct populations of interneurones capable of releasing either GABA or glycine. In the cortex, however, where GABA is about 4 times more potent than glycine (Krnjevic & Phillis, 1963;Curtis et al, 1968a;Kelly & Krnjevic, 1969;Johnson, Roberts & Straughan, 1970), Kelly & Kmjevic (1969) found that only GABA mimicked the effect of the inhibitory transmitter on the cell membrane. GABA was also considered a more effective depressant than glycine on the spike-discharge of Deiters' neurones (Bruggencate & Engberg, 1969Obata, Takeda & Shinozaki, 1970), Purkinje cells of the cerebellum (Kawamura & Provini, 1970;Curtis et al, 1971b) and the mitral cells of the olfactory bulb (Nicoll, 1971), three situations where the inhibitory transmitter may well be GABA.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was the principal reason for the rather lower percentage utility of bicuculline as compared with some of the other substances examined (Table 1). R. G. Hill, M. A. Simmonds and D. W. S!raughan Strychnine has been shown to antagonize glycine depression of spinal and cortical neurones (Curtis, Hosli & Johnston, 1968;Johnson et al, 1970) and, in addition, large currents of strychnine can have some antagonistic effects on GABA responses in the cortex (Johnson et al, 1970;Biscoe et al, 1972). The present study confirms that strychnine can exert a weak GABA antagonist action and also indicates that it may sometimes potentiate GABA depressions.…”
Section: Control Agonistsmentioning
confidence: 99%